Analisis Penilaian Saham Terhadap Keputusan Berinvestasi Pada Perusahaan PT Darma Henwa Tbk - Anwar, Anwar (Politeknik Sawunggalih Aji, 2024)
This study aims to analyze stock valuation in relation to investment decisions in PT Darma Henwa Tbk. (DEWA) using the Price Earning Ratio (PER) method. This method calculates the fair value of stocks by dividing the stock price by earnings per share. The study utilizes secondary data such as financial statements, annual reports, and DEWA's stock price data from 2019. It also includes comparative data from several similar companies listed on the Indonesia Stock Exchange (BEI). Descriptive analysis and SWOT analysis are employed to describe DEWA's profile, financial ratios, and fair stock value, as well as to identify the strengths, weaknesses, opportunities, and threats affecting the company. The results of this research indicate that DEWA's stock is overvalued, meaning its market price exceeds its fair value. This is attributed to the company's unsatisfactory financial performance, particularly in terms of solvency and efficiency, and the unfavorable market conditions in the mining sector. Therefore, this research recommends that investors seek alternative investments that are more profitable and aligned with their risk profile.